2018
DOI: 10.1155/2018/9873471
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Expression of Genes Involved in Proteoglycan/Glycosaminoglycan Metabolism during Skin Development

Abstract: Glycosaminoglycans are important for cell signaling and therefore for proper embryonic development and adult homeostasis. Expressions of genes involved in proteoglycan/glycosaminoglycan (GAG) metabolism and of genes coding for growth factors known to bind GAGs were analyzed during skin development by microarray analysis and real time quantitative PCR. GAG related genes were organized in six categories based on their role in GAG homeostasis, viz. (1) production of precursor molecules, (2) production of core pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…163 Moreover, it was found that sulfatase 1 is upregulated during mouse embryonic skin development and is likely involved in cellular signaling. 85 Taken together, the three enzymes that were found in the datasets regulate sulfation patterns of GAGs, which in turn modulates the bioactivity. The GAG heparan sulfate (HS) binds many proteins, such as growth factors, that reside in the ECM and the interaction of HS-binding proteins and receptors is modulated by HS proteoglycans.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…163 Moreover, it was found that sulfatase 1 is upregulated during mouse embryonic skin development and is likely involved in cellular signaling. 85 Taken together, the three enzymes that were found in the datasets regulate sulfation patterns of GAGs, which in turn modulates the bioactivity. The GAG heparan sulfate (HS) binds many proteins, such as growth factors, that reside in the ECM and the interaction of HS-binding proteins and receptors is modulated by HS proteoglycans.…”
Section: Discussionmentioning
confidence: 97%
“…Instead, the expression of genes involved in GAG biosynthesis provides information on the regulation of GAGs during biological processes. A paper published in 2018 by Uijtdewilligen et al provides a curated list of genes involved in proteoglycan/glycosaminoglycan metabolism, 85 dividing GAG-related genes into various categories based on their role in GAG homeostasis. The following four categories were selected for use in our comparison analysis: linkage region formation (8 genes), GAG chain polymerization (13 genes), GAG chain modification (32 genes), and GAG chain degradation (19 genes) (the complete gene list is available in Table S2 †).…”
Section: Identification Of the Matrisome And Gag-related Componentsmentioning
confidence: 99%
“…Due to their structure and composition, GAGs are capable of binding to many components [31][32][33][34][35][36][37] .…”
Section: Introductionmentioning
confidence: 99%